Adaptive modulation and interference cancellation techniques for MIMO-OFDM wireless networks. (2018) - Ahmed, Ali Mundeth; Jasmin, Erakkath Abdu
Multiple-input multiple-output antenna-orthogonal frequency division multiplexing (MIMO-OFDM) is one of the most wanted wireless broadband technology and transmission systems that has been accepted as the basis of fourth generation (4G) wireless communication is MIMO-OFDM. It is so flexible and adaptable to stay in power even in the coming up 5G technologies. The relative motion of the transmitter and receiver can bring alteration in the channel within the time period of an OFDM, hence OFDM causes loss of orthogonally between sub carrier which results in inter-carrier interference. In order to overcome these issues, an adaptive modulation and interference cancellation technique for MIMO-OFDM wireless network are proposed. Along with interference cancellation technique, adaptive modulation is used to meet the required BER performance by selecting suitable modulation modes based on the channel condition. Doppler assisted channel estimation method is used to estimate the channel. Also, inter channel/carrier interference (ICI) cancellation scheme is used to integrate the parallel interference cancellation together with the decision statistical combining (PIC-DSC) module to detect the data and transmit it to the estimator to iteratively refine the channel and give interference free channel. Simulation results shows that the proposed method improves the BER performance of the system.